Challenges associated with implementing anti-doping policy and programs in Africa - Ruwuya, Jonathan; Juma, Byron Omwando; Woolf, Jules (Frontiers in Sports and Active Living, 2022)
Concerns regarding the capability of the International Olympic Committee to address doping in sport catalyzed the formation of the World Anti-Doping Agency (WADA) in 1999. In its establishment phase, WADA sought geopolitical legitimacy and support from governments (including non-Western states) for financing and acceptance. Africa was not considered during WADA's creation, relegating African states to a passive role in the global anti-doping program, and yet is still subject to the strict compliance requirements for WADA's global policy. African countries face challenges establishing anti-doping support structures and implementing the universal policy, including competing macro-level policy demands that favor addressing legacies of colonialism and human capacity development. To develop robust anti-doping support structures, African nations must spearhead anti-doping initiatives by leveraging existing infrastructure and encouraging collaborations between NADOs such that capacity can be built for policy implementation.